2007
DOI: 10.1073/pnas.0610140104
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogeny reveals eusociality evolved twice in vespid wasps

Abstract: Eusocial wasps of the family Vespidae are thought to have derived their social behavior from a common ancestor that had a rudimentary caste-containing social system. In support of this behavioral scenario, the leading phylogenetic hypothesis of Vespidae places the eusocial wasps (subfamilies Stenogastrinae, Polistinae, and Vespinae) as a derived monophyletic clade, thus implying a single origin of eusocial behavior. This perspective has shaped the investigation and interpretation of vespid social evolution for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 39 publications
8
91
0
2
Order By: Relevance
“…The prevalence of primary polygyny (following pleometrosis) in the tropical stenogastrine and polistine wasps is therefore consistent with the maintenance of individual totipotency, as options for direct fitness benefits either in a co-founded nest or elsewhere remain a realistic option. The stenogastrine clade never evolved obligate eusociality, whereas the sister clade consisting of the polistine and vespine wasps has a single transition towards obligate eusociality in the ancestor of the vespines that adopted single queen breeding (Hines et al 2007). This scenario was already conceptualized by Wheeler (1928), and by Wilson (1971) who wrote: 'The life cycle of the vespines is basically similar to that of Polistes, except that the queen is not joined by auxiliaries during nest founding in spring'.…”
Section: Evidence For Ancestral Lifetime Monogamy In Eusocial Lineagesmentioning
confidence: 99%
“…The prevalence of primary polygyny (following pleometrosis) in the tropical stenogastrine and polistine wasps is therefore consistent with the maintenance of individual totipotency, as options for direct fitness benefits either in a co-founded nest or elsewhere remain a realistic option. The stenogastrine clade never evolved obligate eusociality, whereas the sister clade consisting of the polistine and vespine wasps has a single transition towards obligate eusociality in the ancestor of the vespines that adopted single queen breeding (Hines et al 2007). This scenario was already conceptualized by Wheeler (1928), and by Wilson (1971) who wrote: 'The life cycle of the vespines is basically similar to that of Polistes, except that the queen is not joined by auxiliaries during nest founding in spring'.…”
Section: Evidence For Ancestral Lifetime Monogamy In Eusocial Lineagesmentioning
confidence: 99%
“…Eusociality has arisen independently at least 12 times in the insects (5)(6)(7)(8), and eusocial insects have all converged on the following three characteristics: reproductive division of labor, cooperative brood care, and overlapping generations (9). Additionally, despite sharing this core set of traits, there are many differences among eusocial lifestyles, which may be related to ecological, phylogenetic, or other factors specific to particular eusocial lineages (1).…”
mentioning
confidence: 99%
“…The first application of cladistic analysis to higher-level relationships within Vespidae by Carpenter (1982) confirmed Bradley's assessment, and this was corroborated when fossil data were added (Carpenter and Rasnitsyn, 1990). Recently, Hines et al (2007) published a molecular analysis that showed Euparagiinae not as sister group to the other Vespidae, but rather as closely related to Masarinae. However, their analysis is deficient is many respects, notably in failing to consider all previously published data, and reanalysis of their data (Pickett and Carpenter, in prep.…”
Section: Systematicsmentioning
confidence: 90%